Exploring the Effects of Carbon Pricing and Carbon Quota Control on the Energy Transition Towards Carbon Neutrality: A Computable General Equilibrium Analysis of the Zhejiang Region of China - Bo Shi; Qiuhui Jiang; Minjun Shi; Shunsuke Managi (Energies)
The pathway towards carbon neutrality in regions with a relatively light industrial structure and scarce renewable energy resources presents a challenge when balancing energy efficiency improvements with the expansion of renewable energy. Therefore, this study investigates the effectiveness of carbon pricing and carbon quota control as regional carbon abatement policies. The findings demonstrate that carbon taxes are less effective than carbon emission quota control in economic growth and carbon abatement due to their weaker impact on energy efficiency enhancement and structural transition in the energy and industrial sectors. Moreover, stricter carbon pricing, determined by carbon emission goals, leads to greater reduction in sectoral carbon intensity but slower GDP growth caused by the accelerated decline of manufacturing and infrastructure industries compared to carbon intensity quota policies. In addition, carbon pricing derived from carbon emission and intensity quota policies increases reliance on domestically imported electricity, which is constrained by the availability of renewable energy resources.